2019
DOI: 10.1155/2019/8074827
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characterization of Thermoplastic Aligner Materials: Recommendations for Test Parameter Standardization

Abstract: Background. Understanding of the different mechanical properties of thermoplastic materials is essential for a successful aligner treatment and further developments. However, data of previous material testing studies are scarcely comparable. Aim of the current study was to evaluate the different test parameters to lay the foundations for guidelines for future, more standardized three-point-bending aligner material tests. Materials and Methods. Several parameters concerning the specimen preparation and experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 27 publications
3
40
1
3
Order By: Relevance
“…Several studies reported that mechanical and physical properties of orthodontic aligner materials may change after thermoforming, cyclic mechanical loading and/or thermocycling processes as well as after clinical use [3]. Thus mechanical properties should be determined after thermoforming and under the influence of thermocycling and cyclic loading [2,8,10,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that mechanical and physical properties of orthodontic aligner materials may change after thermoforming, cyclic mechanical loading and/or thermocycling processes as well as after clinical use [3]. Thus mechanical properties should be determined after thermoforming and under the influence of thermocycling and cyclic loading [2,8,10,21].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of test geometry, the amount of thickness reduction and the change of material parameters due to drawing over a three-dimensional (3D) object were to be analyzed as well. Test geometries described by Elkholy et al [8] and Kwon et al [14] were used.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of CA are better aesthetic, higher patient acceptance and better life quality. CA treatment results in less pain for patients compared to a traditional fixed treatment [4][5][6][7][8][9][10][11][12][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is widely used in many applications such as displays, vending machine windows, food packaging, cosmetics and electronics. This material is an amorphous copolymer of PET but, unlike this one, it is not able to undergo strain-induced crystallization independently of the stretching rates and temperatures used during processing (Dupaixa and Boyce, 2005;Elkholy et al, 2019). Due to the favorable combination of excellent esthetic characteristics, formability, high mechanical strength, excellent flexibility and high impact resistance (Sheridan et al, 1994;Sheridan and Armbruster, 1999;Oh and Wang, 2007;Lloyd et al, 2001), this material has gained great interest in the last decade in the medical device industry.…”
Section: Introductionmentioning
confidence: 99%
“…Other experimental studies report results from tensile tests or uniaxial and plane strain compression tests conducted over a wide range of temperatures and strain rates (Eliades and Bourauel, 2005;Kwon et al, 2008;Pascual et al, 2010;Zhang et al, 2011;Elkholy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%